Optimal Placement of Sensors in Mission-specific Mobile Sensor Networks - Hicham Ouchitachen; Abdellatif Hair; Najlae Idrissi (Institute of Advanced Engineering and Science, 2015)
Placement of nodes has been the major challenge in wireless sensor networks. The data reported from a sensor is only useful when the position of that sensor is found. In this context, several techniques have been proposed to conserve power consumption and to prolong the lifetime of the wireless sensor networks. In this paper, we propose a new algorithm that accurately finds the best locations of sensors while minimizing the average energy consumed in the network. More precisely, we consider a critical network in each sensor satisfying its own missions and depending on its locations. In addition to fulfill their mission, the sensor tries to maintain a good neighboring nodes quality. we determine the location of node by using two criteria: the cost and the quality of communication. The aim of this work is to develop a new algorithm so as to solve the complicated optimization problem posed in this case while minimize the total energy consumption. Our simulation results demonstrate that our algorithm is very advantageous in terms of convergence to the appropriate locations.